Choice and justification of the method of titanium welding with platinum - Anatolii Sanin; Ihor Mamchur; Tetiana Nosova; Stella Mamchur (Challenges and Issues of Modern Science)
The purpose of this work is to select a technology for joining platinum foil and titanium, as well as to develop welding modes. The analysis showed that diffusion welding of platinum foil with titanium alloys over a contact area of more than 1000 mm², ensuring continuous penetration and maintaining the original dimensions of the platinum foil requires additional research. Analysis of the platinum-titanium system shows insignificant solubility of titanium in low-temperature modification platinum and higher solubility in high-temperature modification of titanium. Intermetallic compounds Ti3Pt, TiPt, TiPt3 are also formed. The use of fusion welding will lead to the formation of all of the listed phases in the molten zone. It is not possible to regulate their length. The use of diffusion welding in a vacuum makes it possible to regulate the phase composition by changing the welding parameters. To study the phase composition of the platinum-titanium diffusion zone, the following techniques were used: metallographic analysis; X-ray diffraction analysis; X-ray microspectral analysis; electron microscopic analysis. Microstructural studies were carried out on cross-sectional samples at magnifications x500, x4000. Microstructural studies were carried out on cross-sectional samples at magnifications x500, x4000. The detailed structure of diffusion zones was studied using a scanning electron microscope (SEM). The determination of the phase composition of diffusion zones was carried out using the DRON-1.5 installation. Analysis was carried out to identify phases and phase mixtures. Micro-X-ray spectral analysis was carried out on a Cameca device using the scanning method and determining the composition by elements with a distance between points of 2 μm in the direction perpendicular to the welding surface. The formation of the welding zone is determined by diffusion processes and affects the strength of the joint. The holding time is the most significant factor determining the degree of development of diffusion processes.